PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DENGAN BANTUAN MEDIA MONOPOLI PINTAR UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI “AKU BAGIAN DARI MASYARAKAT” KELAS 3A SD NEGERI GENDING II KABUPATEN PROBOLINGGO - M. Syaiful Hilal Muttaqin; Ribut Prastiwi Sriwijayanti; Shofia Hattarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the results of initial observations carried out at SD Negeri Gending 2 class 3A, it was found that student learning outcomes in IPAS subjects were still low. This is due to the lack of use of innovative learning models, so many teachers still apply conventional methods. As a result, students are less active and less interested in learning, especially in the material “I am Part of Society,” where the achievement is still below the Minimum Completeness Criteria (KKM). This study aims to find effective solutions in improving student learning outcomes through the application of the Teams Games Tournament (TGT) learning model assisted by Smart Monopoly media. Researchers used a systematic and reflective Classroom Action Research (PTK) method, which was carried out in three stages, namely pre-cycle, cycle 1 and cycle 2. Each cycle includes the stages of planning, implementation, observation, and reflection to find effective solutions to improve student learning outcomes The results showed that after the application of the TGT learning model assisted by Smart Monopoly in cycle II, there was a significant increase in student learning outcomes. The average student score increased from (44%) to (66%) In addition, the number of students who achieved mastery increased to 17 students (94%), while 1 student was still not complete. Thus, cycle II has met the expected completeness criteria. It can be concluded that the application of the TGT learning model assisted by Monopoly Pintar improves student learning outcomes and makes learning more interesting. This research can be developed with broader materials and diverse media to increase learning motivation.